Nematode resistance: A useful tool for root-knot nematode (RKN) management in tomato. - Homan Regmi; Johan Desaeger (EDIS)
Tomatoes are a major commodity in Florida, with an estimated production value of $453 million. Among the many pests and diseases that affect tomatoes, nematodes are one of the major problems. Since the ban on methyl bromide, these ubiquitous soil pests have become much more difficult to manage. This 5-page fact sheet written by Homan Regmi and Johan Desaeger and published by the UF/IFAS Entomology and Nematology Department discusses the use of nematode-resistant tomato cultivars as a tool to help manage root-knot nematodes in Florida. http://edis.ifas.ufl.edu/in1250